Material‐Efficient Microfluidic Platform for Exploratory Studies of Visible‐Light Photoredox Catalysis. Issue 33 (17th July 2017) - Coley, Connor W.; Abolhasani, Milad; Lin, Hongkun; Jensen, Klavs F.
Abstract: We present an automated microfluidic platform for in‐flow studies of visible‐light photoredox catalysis in liquid or gas–liquid reactions at the 15 μL scale. An oscillatory flow strategy enables a flexible residence time while preserving the mixing and heat transfer advantages of flow systems. The adjustable photon flux made possible with the platform is characterized using actinometry. Case studies of oxidative hydroxylation of phenylboronic acids and dimerization of thiophenol demonstrate the capabilities and advantages of the system. Reaction conditions identified through droplet screening translate directly to continuous synthesis with minor platform modifications. Abstract : Glow with the flow : An automated photochemistry platform built around a microfluidic oscillatory flow reactor enables efficient investigation of photocatalyzed liquid and gas–liquid reactions in individual 15 μL droplets. The conditions identified through screening are directly adapted to continuous flow synthesis.